2016
DOI: 10.4314/ahs.v16i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, severity and risk factors of allergic disorders among people in south India

Abstract: Background: Allergic disorders are not usually life-threatening conditions but they impair the person's ability to function. It thus adversely affects the psychological wellbeing and quality of life. These implications of allergic disorders can be minimized if strategies are planned for its early identification followed by appropriate interventions. Objectives: To find out the prevalence and risk factors of allergic disorders. Methods: Data was collected by house to house survey among participants aged 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
3
9
0
1
Order By: Relevance
“…The common precipitants of allergic disorders include dust, seasonal changes, and food substances. 18 It is imperative to take a detailed history of allergy and exposure to various allergens while dealing with a case of HE/HES.…”
Section: Discussionmentioning
confidence: 99%
“…The common precipitants of allergic disorders include dust, seasonal changes, and food substances. 18 It is imperative to take a detailed history of allergy and exposure to various allergens while dealing with a case of HE/HES.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their high prevalence and high recurrence rate, allergic diseases pose a serious financial burden for affected households and consume substantial resources in socialized healthcare systems. Thus, the WHO has designated allergic diseases as one of the top disease classes requiring major research and prevention measures in the 21st century [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the reports of a study in India, the prevalence of allergy was 28.7% and the highest rate of allergy was associated with dust (21). Furthermore, the findings of another study indicated that the incidence rate of allergy was age-dependent such that the highest rate of allergy to mites and trees was observed in individuals above 4 years.…”
Section: Discussionmentioning
confidence: 98%